2016
DOI: 10.1136/bcr-2016-216686
|View full text |Cite
|
Sign up to set email alerts
|

Polycythaemia: an unusual presentation of multiple myeloma

Abstract: In contrast to anaemia, polycythaemia is a distinctly uncommon finding in patients with multiple myeloma. We describe the presence of otherwise unexplained polycythaemia in a 57-year-old Caucasian man who was found to have IgG κ multiple myeloma. After treatment of myeloma, the polycythaemia resolved. We reviewed previous reports of polycythaemia associated with multiple myeloma and discuss potential pathophysiological mechanisms that link these 2 conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…One theory that has been posited in attempt to explain this rare association between PCM and polycythemia is that the deposition of monoclonal light chains causes damage in kidney tubules leading to hypoxia, resulting in increased EPO production. The cases mentioned above in which treatment of the PCM ameliorated the polycythemia are compatible with this theory [ 7 ]. This theory seemingly would require the plasma cell malignancy to precede the polycythemia.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…One theory that has been posited in attempt to explain this rare association between PCM and polycythemia is that the deposition of monoclonal light chains causes damage in kidney tubules leading to hypoxia, resulting in increased EPO production. The cases mentioned above in which treatment of the PCM ameliorated the polycythemia are compatible with this theory [ 7 ]. This theory seemingly would require the plasma cell malignancy to precede the polycythemia.…”
Section: Discussionmentioning
confidence: 70%
“…The exclusion of these PV cases leaves a total of six cases in the literature (including this current case of the smouldering variant of PCM which was deemed to be not to be PV due to the absence of the archetypal V617F mutation and elevated EPO levels even though exon 12 mutational studies were not performed), all of which can be characterized as PCM with concurrent polycythemia of undetermined etiology. In three of these cases, the polycythemia significantly preceded the diagnosis of PCM (as in our case), while, in the other two cases, the diseases were diagnosed concurrently [ 7 ]. The initial treatment in all of the cases was phlebotomy, with no known treatment for the myeloma in all of the cases in which the polycythemia preceded the myeloma.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, after review of the literature, we have identified four patients of MM or smoldering multiple myeloma (SMM) with unexplained secondary erythrocytosis. Two patients were diagnosed erythrocytosis years before the detection of MM, and the others were diagnosed simultaneously with secondary erythrocytosis and MM/SMM ( 29 32 ). Their monoclonal proteins have been reported to be IgG κ or IgA λ, which were both seen in TEMPI syndrome.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…5,6 The report on the simultaneous coexistence of PV and MM is rare, with about twenty-four cases reported in the literature. [7][8][9][10][11][12][13][14][15] Most of these reports included patients who had antecedent or concomitant PV or who already developed secondary myeloma after radiation therapy of PV for years. We describe a female patient who presented with NDMM and subsequently met diagnostic criteria of PV well established by extensive laboratory workup for the first time.…”
Section: Introductionmentioning
confidence: 99%